Ecotourism and hunting in Ukraine: development analysis and forecast for the future - Serhii Portiannik; Volodymyr Merchanskyi (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2024)
The development of ecological tourism is important for any country of the European Union, the USA, including Ukraine. An important component of ecotourism in different countries can be a combination of unique ecological, cultural and historical routes with the possibility of active recreation for tourists in the form of fishing or hunting, if there are suitable conditions for this. The territory of Ukrainian communities is rich in natural and cultural and historical objects. Unfortunately, Russian aggression led to the destruction of many unique natural landscapes, forest, hunting grounds, water ecosystems are bombed, not only people die, but also hunting (wild) animals, historical and cultural monuments are destroyed, such as the national literary and memorial the museum of the outstanding Ukrainian writer and philosopher Hryhoriy Savich Skovoroda in Kharkiv region. The aim and objectives of the research ¬ to analyze ecological and hunting tourism in Ukraine before the start of hostilities in the country and to assess the prospects for the development of the ecological tourism industry after the end of hostilities, in peacetime with the simultaneous stable and balanced development of hunting in natural territories that have not undergone ecocide taking into account positive and negative international experience, international norms, rules of environmental activity. The material for research was scientific works, publications of famous domestic and foreign scientists, monographs of others. Increased attention is paid to environmentally safe and economically efficient management of hunting and tourism in the countries of the European Union. In the conditions of the war, it is very difficult to develop ecological and hunting tourism and hunting economy, but in the post-war period, the country will have such opportunities. Today, it is necessary to analyze the state of industries, to take into account the international experience of effective management of natural resources, forest and hunting grounds in the process of reform. Ecological and hunting tourism should become not only economically efficient, but also such that ensures stable recovery, increase in the population of hunting animals, wider use of photo hunting, creation of an opportunity for recovery and psychological rehabilitation of hero warriors, defenders of the country after the war. Different regions of Ukraine have forest and hunting grounds to a greater or lesser extent. It will not be possible everywhere to combine the development of ecological tourism with the development of hunting, but where it can be done, the state should contribute, including by improving the regulatory and legal framework, support business, attract the help of international partners, promote the establishment of an attractive investment climate.